Exogenous aspartic acid alleviates salt stress-induced decline in growth by enhancing antioxidants and compatible solutes while reducing reactive oxygen species in wheat - Sadak, Mervat Sh; Sekara, Agnieszka; Al-ashkar, Ibrahim; Habib-ur-Rahman, Muhammad; Skalicky, Milan; Brestic, Marian; Kumar, Ashwani; Sabagh, Ayman El; Abdelhamid, Magdi T. (Frontiers in Plant Science, 2022)
Salinity is the primary environmental stress that adversely affects plants’ growth and productivity in many areas of the world. Published research validated the role of aspartic acid in improving plant tolerance against salinity stress. Therefore, in the present work, factorial pot trials in a completely randomized design were conducted to examine the potential role of exogenous application of aspartic acid (Asp) in increasing the tolerance of wheat (Triticum aestivum L.) plants against salt stress. Wheat plants were sown with different levels of salinity (0, 30, or 60 mM NaCl) and treated with three levels of exogenous application of foliar spray of aspartic acid (Asp) (0, 0.4, 0.6, or 0.8 mM). Results of the study indicated that salinity stress decreased growth attributes like shoot length, leaf area, and shoot biomass along with photosynthesis pigments and endogenous indole acetic acid. NaCl stress reduced the total content of carbohydrates, flavonoid, beta carotene, lycopene, and free radical scavenging activity (DPPH%). However, Asp application enhanced photosynthetic pigments and endogenous indole acetic acid, consequently improving plant leaf area, leading to higher biomass dry weight either under salt-stressed or non-stressed plants. Exogenous application of Asp, up-regulate the antioxidant system viz. antioxidant enzymes (superoxide dismutase, peroxidase, catalase, and nitrate reductase), and non-enzymatic antioxidants (ascorbate, glutathione, total phenolic content, total flavonoid content, beta carotene, lycopene) contents resulted in declined in reactive oxygen species (ROS). The decreased ROS in Asp-treated plants resulted in reduced hydrogen peroxide, lipid peroxidation (MDA), and aldehyde under salt or non-salt stress conditions. Furthermore, Asp foliar application increased compatible solute accumulation (amino acids, proline, total soluble sugar, and total carbohydrates) and increased radical scavenging activity of DPPH and enzymatic ABTS. Results revealed that the quadratic regression model explained 100% of the shoot dry weight (SDW) yield variation. With an increase in Asp application level by 1.0 mM, the SDW was projected to upsurge through 956 mg/plant. In the quadratic curve model, if Asp is applied at a level of 0.95 mM, the SDW is probably 2.13 g plant-1. This study concluded that the exogenous application of aspartic acid mitigated the adverse effect of salt stress damage on wheat plants and provided economic benefits.